University Students’ Perceptions about Teaching Ataturk’s Principles and Turkish Revolution History with Distance Education - Akbaba, Bülent; Kaymakci, Selahattin; Bi̇rbudak, Togay Seçkin; Kilcan, Bahadır (Afyon Kocatepe University, 2016)
This study aimed to reveal students’ views regarding the teaching of the Atatürk’s Principles and History of Revolution (APHR) course by distance education. The survey model was employed in the study. The study group consisted of 645 students attending Karadeniz Technical University and Karabük University. The research results showed that although the participants receiving the APHR course by distance education had a high level interest in history of revolution subjects, they had a low level participation in the APHR course. Most of the participants wanted the APHR course to continue to be taught at higher education level without any change in its content and name. The participants thought that the teaching of the Atatürk’s Principles and History of Revolution accomplished its goals at medium and high levels. Among the problems encountered by the students in the APHR teaching by distance education, the most prominent ones were the inadequacy of the teaching methods employed, exam-oriented instruction, and the insufficiency of the teaching materials used. Traditional lecture and adhesion to textbook continued in distance education, too. It was seen that most of the participants receiving the APHR course by distance education did not attend the lessons regularly and thought that teaching the APHR course by distance education was not beneficial.

Bu araştırmanın amacı uzaktan eğitimle Atatürk İlkeleri ve İnkılâp Tarihi (AİİT) öğretimine yönelik öğrenci görüşlerini ortaya koymaktır. Tarama modelinde gerçekleştirilen araştırmanın çalışma grubunu Karadeniz Teknik Üniversitesi ve Karabük Üniversitesinde öğrenim gören toplam 645 öğrenci oluşturmaktadır. Araştırmanın sonuçlarına göre, uzaktan eğitimle AİİT dersi alan katılımcıların inkılâp tarihi konularına ilgi düzeyi yüksek olmakla birlikte AİİT derslerine katılım düzeyleri düşüktür. Katılımcıların çoğunluğu AİİT dersinin yükseköğretim düzeyinde okutulmasının devam etmesini, içeriğinin ve dersin adının değişmemesini istemektedir. Katılımcılar Atatürk İlkeleri ve İnkılâp Tarihi öğretiminin amaçlarının gerçekleşme düzeyinin orta ve üst düzeyde olduğunu düşünmektedirler. Uzaktan eğitim ile yapılan AİİT derslerinde de öğrencilerin karşılaştıkları sorunlar arasında; derste kullanılan öğretim yöntemlerinin yetersizliği, dersin sınavlara yönelik olarak işlenmesi ve derste kullanılan öğretim materyallerinin yetersizliği dikkat çekmektedir. Düz anlatım yöntemi ve ders kitabı bağımlılığı uzaktan eğitim uygulamasında da devam etmektedir. AİİT dersini uzaktan eğitim yoluyla alan katılımcıların çoğunluğu dersleri düzenli takip etmemekte ve AİİT dersinde uzaktan eğitim uygulamasının yararlı olmadığını düşünmektedir.
Keywords: Atatürk ilkeleri ve inkılâp tarihi dersi; uzaktan eğitim; üniversite öğrencisi; Atatürk’s principles; history of revolution; distance education; university students; 4. Education; 16. Peace & justice